Evaluation of the hepatoprotective effect of methanolic extract of Caulerpa lentillifera against acetaminophen-induced liver toxicity in juvenile zebrafish (Danio rerio) - Kimberly D. Codorniz; Rose Emielle M. Marquina; Alexandra Dominique G. Nolasco; Paula Denise D. Palencia; Sigfredo B. Mata (Universitas Islam Indonesia, 2020)
AbstractBackground: Liver injury is a common reason for drugs to be withdrawn from the market. Treatment options for common liver disease are limited, and therapy with modern medicines may lack effectiveness. Caulerpa lentillifera may have strong antioxidant systems that protect the plant from oxidative damage caused by the environment.Objectives: The main objective of this study was to evaluate the hepatoprotective effect of the methanolic extract of C. lentillifera against acetaminophen-induced liver toxicity in juvenile zebrafish (Danio rerio). Methods: Juvenile zebrafish (aged 1–3 months) were exposed to 10 mikromolar and 25 mikromolar acetaminophen (N-acetyl-p-aminophenol; APAP) to induce liver damage. C. lentillifera methanolic extracts (0.01 mg/L, 0.02 mg/L and 0.03 mg/L), were concomitantly added to individual tanks containing 0.01 M or 0.025 M APAP. The positive control group was treated with N-acetylcysteine/NAC (0.01 M) and silymarin (0.01 mg/L, 0.02 mg/L and 0.03 mg/L). Hematoxylin and Eosin (H&E) staining revealed the extent of liver injury through the presence of hepatic necrosis, vacuolization, leukocyte infiltration, and ballooning. The antioxidant mechanism of hepatoprotective activity was assessed by a DPPH free radical scavenging assay.Result: C. lentillifera extracts reduced the mortality of juvenile zebrafish when simultaneously exposed to APAP. Upon histopathological examination of the liver tissue of juvenile zebrafish, the group treated with the 0.01 M APAP together with the highest concentration of C. lentillifera extract showed minimal liver injury compared to the groups exposed 0.025 M APAP. However, the DPPH free radical scavenging assay performed using 24–36 mg/mL C. lentillifera extracts showed a minimal effect on the free radical scavenging activity.Conclusion: The histopathological analysis of the liver showed that C. lentillifera extract prevented the progression of liver damage caused by APAP. The results of DPPH free radical scavenging assay indicated that the hepatoprotective activity of C. lentillifera extract might have other antioxidant mechanisms aside from free radical scavenging. In order to effectively assess the improvement in the survival rate of juvenile zebrafish, longer exposure in the treatments is recommendedKeywords: C. lentillifera; juvenile zebrafish; hepatoprotective; drug-induced liver injury (DILI)